Left omental artery bleeding in two patients with segmental arterial mediolysis successfully isolated with coil embolization - Nishiyama, Tomoya (CVIR Endovasc, 2020)
BACKGROUND: Segmental arterial mediolysis (SAM) is a rare, nonatherosclerotic, noninflammatory arteriopathy of unknown etiology, rarely involving omental artery (OA). No case reports have described left OA bleeding successfully treated with transarterial embolization (TAE) with coils. This report describes two cases of SAM-affected left OA bleeding successfully embolized using isolation technique with coils, recognizing the potential for the greater omentum to have arterial collateral network between OAs. CASE PRESENTATION: Case 1. A 55-year-old male with no significant past medical history presented with an acute abdomen. Contrast-enhanced computed tomography (CT) revealed possible hemorrhagic ascites involving the left portion of the greater omentum and dilated, stenotic change of the left OA with a possible hematoma. SAM-associated left OA bleeding was suspected. Given its acute-angled branching from a splenic artery or branch and long, tortuous catheter-trajectory, we used a triaxial catheter system. Left OA angiography revealed the proximal dilated, stenotic change and a distal pseudoaneurysm. Isolation was successfully performed with coils. Because he had no abdominal pain or progressive anemia, he was discharged on hospital day 5. Neither recurrence nor new SAM-associated findings were observed during two-years of follow-up. Case 2. A 60-year-old-man with no significant past medical history presented with an acute abdomen. CT revealed similar finding as Case 1. SAM-associated left OA bleeding was suspected. Left OA angiography revealed proximal dilated, stenotic change with distal occlusion. Despite having no signs of active bleeding, review of the CT and angiography findings suggested the left OA as the bleeding site. Given proximal embolization at this point could lead to incomplete hemostasis or rebleeding via the arterial collateral network between OAs, an attempt was made to navigate the microcatheter into the distal side beyond the occlusion. Distal left OA angiography confirmed that the distal OA over the occlusion was intact and directly communicated with a right OA arising from right gastroepiploic artery. The SAM-associated lesion was successfully isolated with coils. Because he had no abdominal pain or progressive anemia, he was transported to another hospital on hospital day 3. Neither recurrence nor new SAM-associated findings were observed during two-years follow-up. CONCLUSION: SAM can involve left OA and be controlled using an isolation technique with coils.